Monitorování výskytu a šíření HIV/AIDS v ČR - Brůčková, Marie; Linka, Marek; Vandasová, Jana; Malý, Marek (Iga MZ ČR, 2007)
HIV/AIDS topic in public health. National monitoring programme, HIV and AIDS reporting system, compatibility with European monitoring programme. HIV/AIDS epidemiology, molecular epidemiology, surveillance in population at high risk of HIV infection. Trens in spread of HIV infection in the Czech Republic. HIV genetic studies, identification of HIV-subtypes and variants, study of antiretroviral resistance in HIV isolates
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: dermatovenerologie; kontrola infekčních nemocí; Genome, Human; Monitoring, Immunologic; HIV Infections; Acquired Immunodeficiency Syndrome; Czech Republic; epidemiologie; infekční lékařství; Communicable Disease Control; AIDS; genom lidský; monitorování imunologické; Česká republika; HIV infekce